A STUDY ON THE DOMINATING MECHANISMS AND PARAMETERS INFLUENCING THE PHYSICAL PROPERTIES OF ARIAKE CLAY - Asuri Sridharan; Ahmed El-Shafei; Norihiko Miura (International Association of Lowland Technology, 2000)
Extensive investigations have been carried out on the engineering behavior of Ariake clays. The range of variation pf physical properties for Ariake clay is very high. A better understanding of the engineering behavior necessitates the understanding of their physical and physico-chemical behavior. The factors influencing the physical properties are the clay mineral type, percent clay size fraction, and the pore medium chemistry. Both ion concentration and type of ion can vary significantly. Comparison of Ariake clay with change in ion concentration has been examined with bentonite clay treated with artificial seawater and it has been found that two dominating mechanisms control their liquid limit behavior. As concentration and/or ion valence increase, flocculation takes place and attractive force increase, leading to increase in liquid limit. These two mechanisms oppose each other in inluencing the liquid limit. However both mechanisms co-exist and depending upon the factors like relative proportion of various clay minerals present, percent clay size fraction and type and concentration of various ions, one of the mechanisms dominates.